McCain’s Messages: Matrices and Mathematical Practices (pp. 42–50) - Long, Valerie N; Sharp, Brian (Ohio Journal of School Mathematics, 2020)
The authors discuss what happened when twenty-two middle school students were introduced to the structure of matrices as they studied how John McCain and other prisoners of the Vietnam War used the tools to communicate. In addition to sharing the results of the historically based lesson, this article describes how the students engaged in many of the Mathematical Practices from the Common Core State Standards for Mathematics.